Нові матеріали про архео-спелеологічний об’єкт в уроч. Турецька Криниця на Буковині - Калініченко, Віталій; Ільків, Микола; Пивоваров, Сергій (My University, 2018)
Aim of investigation.The article describes a multilayered archaeological and speleological object of medieval time near the village Zelena Lipa of Khotyn district, which is located on the high right bank of the Dniester river, in the terrain Turetska Krynytsia (Turkish Well). As a result of the research of the Slavic expedition of the Institute of Archeology of the USSR in 1982 (heads of expedition – I.P. Rusanova, B.O. Tymoshchuk) found materials raykovetska and Kyiv Rus cultures and the archaeological object is identified as a pagan sanctuary with the “idol temple” and sacrificial well.The speloarcheological study of the object was carried out in the 1980-1990-s by B.T. Ridush. In connection with the specifics of the object for its study different methods of research were used: descriptive; generalization – for the analysis of historiography and research history; stratigraphic – to characterize the cultural layers of the object, determine its relative chronology; typological – for the study of individual finds; comparative – for comparing the results of archaeological, written and geological materials. With the help of natural analyzes, in particular spectral, the elemental composition of the metal found on the monument was identified. Scientific novelty.The systematization of the results of the study of the object in the thesis has been carried out in the terrain Turetska Krynytsia (Turkish Well) researchers of the pre-revolutionary and soviet times, the period of state independence, and also analyzed the different thoughts on the interpretation of the object. The results of the survey of the area in 2011 by the intelligence detachment under the direction of S.V. Pyvovarov and the results of spectral analyzes of amorphous copper ingots, conducted by T.Y. Goshko, are presented. For the first time, an assumption was made of the connection of the object with the copper smelting business of the ancient population of the region. Conclusions. It is proved that human activity in the territory of the object and in its surroundings took place not only in the middle ages, but also in the early new time. Newly-discovered materials, along with other mediated data, allow us to suggest that the object under investigation could be an ancient mining and metallurgical centre.
New materials about archeo-speleological object in the terrain Turetska Krynytsia in Bukovina
Keywords: архео-спелеологічний об'єкт; Турецька Криниця; язичницьке святилище; мідні злитки; гірничо-металургійний центр